2018
DOI: 10.1038/s41594-018-0091-z
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of mRNA structure dynamics identify embryonic gene regulatory programs

Abstract: RNA folding plays a crucial role in RNA function. However, knowledge of the global structure of the transcriptome is limited to cellular systems at steady state, thus hindering the understanding of RNA structure dynamics during biological transitions and how it influences gene function. Here, we characterized mRNA structure dynamics during zebrafish development. We observed that on a global level, translation guides structure rather than structure guiding translation. We detected a decrease in structure in tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 72 publications
6
86
0
Order By: Relevance
“…Recent reports showed that ribosomes reduce the overall degree of structure in the coding sequence of the transcriptome (Adivarahan et al, 2018;Beaudoin et al, 2018;Mizrahi et al, 2018;Mustoe et al, 2018). In addition, several studies have shown that AGO target sites are less efficiently recognized if they are embedded within a strong structure (Ameres et al, 2007;Beaudoin et al, 2018). Here, we show that ribosome-dependent unfolding of mRNA structures stimulates AGO-target interactions, providing a direct, causal link between mRNA translation and AGO2-target binding.…”
Section: Paradoxical Roles Of Ribosomes In Controlling Ago2-mrna Targmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports showed that ribosomes reduce the overall degree of structure in the coding sequence of the transcriptome (Adivarahan et al, 2018;Beaudoin et al, 2018;Mizrahi et al, 2018;Mustoe et al, 2018). In addition, several studies have shown that AGO target sites are less efficiently recognized if they are embedded within a strong structure (Ameres et al, 2007;Beaudoin et al, 2018). Here, we show that ribosome-dependent unfolding of mRNA structures stimulates AGO-target interactions, providing a direct, causal link between mRNA translation and AGO2-target binding.…”
Section: Paradoxical Roles Of Ribosomes In Controlling Ago2-mrna Targmentioning
confidence: 99%
“…Recent studies have also revealed that mRNAs can undergo structural rearrangements throughout an mRNA's life. For example, when zebrafish embryos undergo the maternal-to-zygotic transition (Beaudoin et al, 2018), or as mRNAs transition from the nucleus to the cytoplasm (Adivarahan et al, 2018;Sun et al, 2019), or upon translation of mRNAs by ribosomes (Beaudoin et al, 2018;Mizrahi et al, 2018;Mustoe et al, 2018). While these studies demonstrate that mRNAs can adopt distinct structural conformations, they provide limited insights into the dynamics of mRNA structure, especially on the short timescales at which AGO-target interactions likely occur.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, synonymous codons have been shown to alter elongation rate either by altering the rate of decoding (59) or by altering downstream mRNA stability, which can impede ribosome translocation (60). In vivo, there is some evidence that stable mRNA stem-loop structures can alter the elongation rate of the ribosome (61-63), although other studies have detected no difference (38,64,65), likely due to destabilization of mRNA structure by polysomes and/or the helicase activity of the ribosome. Although the overall predicted mRNA stability of the WT and Shuf1 genes are similar, a predicted stable 3' stem-loop structure in Shuf1 is not present in the WT coding sequence ( Fig.…”
Section: Mrna Secondary Structural Stability Does Not Explain Shuf1 Gmentioning
confidence: 99%
“…This method can effectively detect the structure of mRNA in vivo at the transcriptome level. In recent years, an increasing number of studies have used this method or improved techniques, such as structure-seq, CIRS-seq, and DMS-MaPseq, to detect mRNA structures (12)(13)(14)(15)(16)(17)(18). Currently, there are several databases collecting in vivo mRNA structure information: RMDB (https://rmdb.stanford.edu/browse/), FoldAtlas (http://www.foldatlas.com/), and Structure Surfer (http://tesla.pcbi.upenn.edu/structuresurfer/) (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%